An Experiment in Methods: Speech Act Theory in the Poems of Wallace Stevens - Gilbert, Stephen W (Sincronía, 2026)
This article proposes a methodological experiment in poetic analysis by applying speech act theory to two key poems by Wallace Stevens: “The Emperor of Ice Cream” and “The Snow Man.” The author argues that, without attempting a totalizing explanation of the poem, speech act theory helps clarify critical moments in the reading process in which readers respond to implicit illocutionary and perlocutionary forces within the text. The analysis focuses on the line “Let be be finale of seems,” highlighting its ambiguity between imperative and declarative readings, an ambiguity that compels the reader to take an active role in meaning-making. Drawing on J. L. Austin, Paul Grice, and Sperber and Wilson, the article examines how Stevens employs explicit and implicit imperatives to stage the poem, transforming the reader into an agent who organizes spaces, actions, and meanings. Reading is thus understood as a form of performance rather than passive reception. The comparison with “The Snow Man” reinforces this argument by showing how the poem invites readers to adopt a specific perceptual stance—“a mind of winter”—through gently implied illocutionary requirements. The article concludes that speech act theory, when applied cautiously, is particularly productive for understanding the participatory, performative, and ethical dimensions of Stevens’s poetry.